The Effect of Capital Structure and Company Size on Company Value in Food and Beverage Sub-Sector Manufacturing Companies in 2020-2022 - Husna, Husna; Loppies, Lilian Sonya; Wenno, Meiske (ProBisnis : Jurnal Manajemen, 2024)
This study aims to determine the effect of capital structure and company size on company value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The population of this study were 26 companies and the sample of this study were 17 companies after outliers were made so that the number of observation samples was 51 data used. The sampling technique in this study was purposive sampling technique. This research test uses Eviews software, with panel data regression testing. The results showed that partially the capital structure has no effect on company value while the size of the company partially has a negative effect on company value. then simultaneously (together) the capital structure and company size affect company value pt).